EFFECTIVENESS OF JIGSAW TYPE COOPERATIVE LEARNING MODEL ON THE MATHEMATIC COMMUNICATION SKILLS OF STUDENTS IN SMP UNGGULAN AISYIYAH BANTUL - Kutrotul Ngilmah; Uswatun Khasanah (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2017)
The Learning model applied in SMP Unggulan ‘Aisyiyah Bantul featured still tends to be teacher’s centered and makes students become passive in the process of learning so that student learning outcomes are still low. Jigsaw is one of many kinds of teaching and learning model which provides opportunities to the students to be actively involved in the class activity. The objectives of this research are (1) to know the diversities in the math learning marks of the eighth-grade students which are taught using the conventional learning model in the odd semester of SMP Unggulan ‘Aisyiyah Bantul in the academic year of 2016/2017, (2) to know the effectiveness of the cooperative learning model type Jigsaw towards the conventional learning model to the eighth-grade students in the odd semester of SMP Unggulan ‘Aisyiyah Bantul in the academic year of 2016/2017. This research used the quantitative research method. The population of the research was the eighth-grade students in the odd semester of SMP Unggulan ‘Aisyiyah Bantul in the academic years of 2016/2017. To obtain the sample, this research used the random sampling technique. As the sample, this research managed the VIII B class as the Experiment Class and VIII A as the Controlled Class. A test was applied for the data collecting technique of this research. To calculate the instrument validity and reliability, this research used the product-moment correlation and the Alpha formula. The data analyzing technique of this research are the t-test, the normality test used the Chi-Quadrate formula, and the homogeneity test used the Bartlett test. Based on the research findings at the 5% significance level and a degree of freedom of 39, thus the accumulations are (1) ttable= 1,6835 and tcount = 2,2470. It collected tcount>ttable so H0 is rejected. Henceforward, there are diversities in the math learning marks of the students who were taught using the cooperative learning model type Jigsaw towards those which were taught using the conventional learning model. (2) ttable= 1,6835 and tcount= 2,2470, collected tcount>ttableso H0 is rejected. To put it briefly, the cooperative learning model type Jigsaw is more effective than the conventional learning model towards math learning marks.